Second Line Drugs Resistant Mycobacterium Tuberculosis in Multi-Drug Resistant Tuberculosis Patients - Tuladhar, Pranita; Khadka, Dhruba Kumar; Banjara, Megha Raj; Tuladhar, Reshma (Journal of Institute of Science and Technology, 2018)
With an increase in Multi-drug resistant tuberculosis (MDR-TB), there is a need of second line drug susceptibility test that helps in early diagnosis and minimize the risk of other powerful drug resistant Mycobacterium tuberculosis. The aim of this study was to determine second line drugs (ofloxacin, kanamycin, capreomycin) resistance pattern in MDR-TB isolates and to determine the prevalence of pre-Extensively drug resistant tuberculosis (pre-XDR-TB) and XDR-TB in MDR-TB patients. The study was conducted from February to September 2015 at National Tuberculosis Centre, Thimi, Bhaktapur. MDR-TB (resistant to isoniazid and rifampicin) patients’ sputum samples were processed by Modified Petroff’s method. Out of 92 samples, 57 were found culture positive. Following the species identification of culture positive MDR-TB isolates, second line drug susceptibility test was performed by conventional proportion method. Of 57 MDR-TB isolates, 22 (38.59%) showed resistance to ofloxacin (Ofx), 9 (15.79%) to capreomycin (Cm) and 9 (15.79%) to kanamycin (Km). One XDR-TB (1.8%) resistant to all drugs was detected. Of the remaining, 21(36.8%) were resistant to ofloxacin only and 8(15.4%) were resistant to two drugs i.e.29 (50.9%) were pre-XDR-TB. The prevalence of pre-XDR-TB and XDR-TB was found to be 50.88% and 1.75% respectively. The resistance pattern of second line anti-tuberculosis drugs showed higher ofloxacin resistance in MDR-TB patients. In a nutshell, MDR-TB cases need urgent and timely susceptibility report for second line anti-tuberculosis drugs to help the clinicians start proper drug combinations to treat MDR-TB patients. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, page: 168-174